2011
DOI: 10.1074/jbc.m111.270322
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of a Replication Initiator with Histone H1-like Proteins Remodel the Condensed Mitochondrial Genome

Abstract: Background:The mechanism of kinetoplast DNA (kDNA) remodeling and its function during replication have been unknown. Results: Interactions of the replication initiator protein UMSBP with kDNA-condensing proteins result in kDNA decondensation, promoting its accessibility to topoisomerase II. Conclusion: UMSBP-mediated remodeling may precede and promote the initiation of kDNA replication. Significance: The function of a replication initiator in remodeling a mitochondrial genome is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 48 publications
(46 reference statements)
0
24
0
Order By: Relevance
“…However, protein-protein interactions between CfKAP3 and CfUMSBP can decondense these networks and restore topo IImediated decatenation (14). This indicates that trypanosomatid KAP proteins could have different roles in different species, especially when they have limited homology, such as between CfKAP3 and TbKAP6.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, protein-protein interactions between CfKAP3 and CfUMSBP can decondense these networks and restore topo IImediated decatenation (14). This indicates that trypanosomatid KAP proteins could have different roles in different species, especially when they have limited homology, such as between CfKAP3 and TbKAP6.…”
Section: Discussionmentioning
confidence: 98%
“…The major protein to be involved in minicircle release must be a type II topoisomerase (12,13). More recently, in vitro studies have demonstrated that Crithidia fasciculata universal minicircle sequence-binding protein (CfUMSBP) can decondense CfkDNA networks that had been condensed by CfKAP3 or CfKAP4 (14). CfUMSBP is well known to bind the origin sequence (universal minicircle sequence [UMS]), but CfUMSBPmediated decondensation depends upon interactions between two proteins and not the DNA.…”
mentioning
confidence: 99%
“…Thus, UMSBP apparently has much broader actions than originally thought. Yossi's laboratory has recently shown that UMSBP binds to kDNA networks in another way when the basic DNA-binding proteins CfKAP3 and CfKAP4 are present (68). UMSBP binds to the KAP protein via protein-protein interactions and then binds the DNA to make it more susceptible to topo II.…”
Section: Homologs Is Essential For Growth But Its Function Is Not Ymentioning
confidence: 99%
“…Presumably, it is by the same enzyme that attaches them because this is the only mitochondrial topo II encoded in the nuclear genome. The release mechanism could be related to the interaction of UMSBP and CfKAP3 or CfKAP4, mentioned previously (68).…”
Section: Rna Interferencementioning
confidence: 99%
“…In fact, mutations to proteins of this complex [ 53 , 54 ] show enlarged and potentially more complicated networks. Histone-like kinetoplast associated proteins (KAP) may also be involved in the positioning of minicircles since they are implicated in condensing the kDNA network [ 55 58 ] and in the remodeling of the kDNA structure during different life cycle phases [ 59 ]. Recent experimental works show that these proteins decrease the excluded volume effects of the minicircles and that interaction of KAP3 and KAP4 with the initiator protein, universal minicircle sequence-binding protein, results in decondensation of the kDNA network and increasing accessibility to topoisomerase II.…”
Section: Discussionmentioning
confidence: 99%